Particle tracking analysis of a rotor in ground effect - Rovere, F.; Barakos, G.N.; Steijl, R. (My University, 2021)
Computational fluid dynamics (CFD) is used here to predict the behaviour of ground particles, uplifted by a two-bladed rotor. The main focus is to define a safety area where the presence of particles can be considered safe, and compare this area with other distance based criteria. Using data of three different aircraft, scaling factors have been used to take into account the different size of the small-rotor studied and real case scenarios. The results show how heavier helicopters may generate the most dangerous situations, in terms of presence of particles in a delimited area. Furthermore, parallel strategy is analysed, code performances are compared in terms of number of particles computed and amount of processors used for calculations.